Three Lenses of Analysis for the Study of Tourism Public Policy: A Case from Northern Australia - Pforr, Christof (Channel View Publications, 2005)
The main emphasis of this paper is directed to the interplay of three conceptual perspectives to the study of tourism public policy. To understand the tourism policy process in general, from demands via the policy-making system to outputs and feedback, Easton’s model (1965) of the political system is employed as a basic conceptual framework. With the adoption of a temporal dimension, which takes into account the dynamics of the tourism policy process, the policy cycle model is then applied as a heuristic structural frame. As an additional, third level of analysis the policy network concept is then discussed. This approach identifies the various and multiple ways in which the actors participate in tourism policy-making as well as the complexity of their interactions. It is argued that the interplay of these three models provides an adequate methodological framework, particularly process-oriented in focus, to better understand the complexity of tourism policy-making. The case study of the specific geographical and social formation of the Northern Territory of Australia illustrates the usefulness of this analytical approach..